Distrust in Utopia? Public Perceptions of Corruption and Political Support in Iceland before and after the Financial Crisis of 2008. Issue 4 (31st March 2015) - Erlingsson, Gissur Ó.; Linde, Jonas; Öhrvall, Richard
Abstract : In the middle of the first decade of the twenty-first century Iceland was ranked as the least corrupt country in the world by Transparency International and enjoyed top positions in most comparative indices of governance and development. In 2008 the banking system collapsed and the country found itself in a serious financial crisis, a crisis which some observers believe was caused by clientelism and other forms of behaviour related to corruption. This article sets out to analyse how the crisis affected general political support and, in particular, the importance of perceptions of corruption in that process. Using survey data we show that political support plummeted after the crisis and that public evaluations of the extent of corruption became the most important determinant of support. The results have implications for how we ought to approach the issue of corruption, even in so-called 'least corrupt' settings. The findings also call into question the validity and reliability of frequently used measures of corruption and governance.